Does globalization accelerate economic growth? South Asian experience using panel data - Md Abu Hasan (Journal of Economic Structures, 2019)
The paper investigates the impact of globalization (overall, economic, social, and political) on economic growth of South Asian countries over the period from 1971 to 2014 employing cross-sectional dependence test, Cross sectionally Augmented Dickey-Fuller (CADF) unit root test (Pesaran in J Appl Econ 22(2):265-312 https://doi.org/10.1002/jae.951, 2007), and Pooled Mean Group (PMG) panel cointegration model (Pesaran et al. in J Am Stat Assoc 94(446):621-634, 1999). Results report that overall globalization, economic globalization, and political globalization accelerate economic growth in the long-run; however, the dimensions of globalization have no significant effect in the short-run. Focusing on the individual country regressions, we find the amalgam results, as the characteristics, elasticity, and strength of political, social, and economic institutions are different in the selected countries. The policy implication is that the governments of South Asian countries should realize the importance of globalization as a powerful influencing force and should adopt the new circumstances of globalization quickly and try to find coherent policies to be connected with an evolving world.
Keywords: C33; F02; F40; F62; 330; Economic globalization; Economic growth; Panel data analysis; Pooled mean group